Intersphincteric anal abscess, a rare cause of axial low back pain: A case report (Annals of Medical Research, 2025)
A 60-year-old male patient presented with axial lower back pain. He had suffered from pain for one month. Within a week, the patient's pain had increased, and he experienced additional symptoms of fever, malaise, and weight loss. Lumbar MRI revealed an intersphincteric anal abscess extending to the level of the lower lumbar vertebrae. The patient was then referred to a general surgeon. After drainage of the abscess and administration of broad-spectrum antibiotics, the patient's pain resolved within one week. This case report describes a rare presentation of lower back pain, in which a normal physical examination led to an initial delay in considering an anal abscess. The diagnosis of an advanced intersphincteric abscess was ultimately established by a lumbar MRI, which had been ordered to investigate for possible malignant metastasis.
Keywords: Anal abscess; Low back pain; Analgesia